2022
DOI: 10.4038/jas.v17i3.9922
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Nematicidal Potential of Leaf Extracts of <em>Adansonia digitata</em> and <em>Khaya senegalensi</em>s on Root Knot Nematode (<em>Meloidogyne incognita</em>) Associated with Cabbage

Abstract: Purpose: Cabbage, an indispensable vegetable is often plagued by Meloidogyne incognita, a circumstance which lessens yield. Extracts of Khaya senegalensis and Adansonia digitata were appraised for possible nematicidal activity to check the menace of M. incognita sequel to the undesirable effect of synthetic nematicides in the environment.Research Method: Leaf materials were extracted in organic and aqueous extracts. The extracts were used as soil admix at 0, 150, 200 and 250 g/Kg soil, in a randomized complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Reports by Viaene and Abawi (1998) specified that amending soil with Sudan grass notably reduced M. hapla reproduction on lettuce resulting in increase of lettuce head weight at harvest. Countless leading-edge studies have shown that extracts of various plant species such as Chenopodium quinoa (Khan and Javaid, 2020), Euphorbia prostrata (Ferdosi et al, 2021a), Bergenia ciliata (Ferdosi et al, 2021b), Eucalyptus officinalis (Fabiyi, 2021c), Khaya senegalensis (Fabiyi, 2022c) and diverse purified active principles contain potent nematicidal compounds (Atolani and Fabiyi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reports by Viaene and Abawi (1998) specified that amending soil with Sudan grass notably reduced M. hapla reproduction on lettuce resulting in increase of lettuce head weight at harvest. Countless leading-edge studies have shown that extracts of various plant species such as Chenopodium quinoa (Khan and Javaid, 2020), Euphorbia prostrata (Ferdosi et al, 2021a), Bergenia ciliata (Ferdosi et al, 2021b), Eucalyptus officinalis (Fabiyi, 2021c), Khaya senegalensis (Fabiyi, 2022c) and diverse purified active principles contain potent nematicidal compounds (Atolani and Fabiyi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plant parasitic nematodes (PPNs) are regarded as a major threat to agricultural crop production causing extensive significant yield losses to farmers worldwide ( Javad et al, 2006;Fabiyi, 2022a). Meloidogyne species also called the root-knot nematodes (RKN) are described as the most devastating due to their wide host range (Bello et al, 2020;Fabiyi, 2021a) and being responsible for yearly crop loss reaching approximately hundred million US dollars worldwide (Chitwood, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to study the nematicidal potential of some plant extracts on the survival and reproduction of plant parasitic nematodes (Fabiyi et al, 2020b;Fabiyi, 2022b). Citrus fruit canning waste, thiarubrinc a root extract from Rudbeckia hirta and common agro wastes such as cocoapod husk, cassava, orange, pineapple and potato, peels have been reported to be an effective control against nematodes with subsequent significant improvements in crop yield (Egunjobi and Olaitan, 1986;Babatola, 1989;Viala et al, 1998;Fabiyi, 2022c).…”
Section: Introductionmentioning
confidence: 99%